Application of the GheOP3S-tool in nursing home residents: acceptance and implementation of pharmacist recommendations. Issue 6 (1st November 2020) - Foubert, Katrien; Muylaert, Peter; Mehuys, Els; Somers, Annemie; Petrovic, Mirko; Boussery, Koen
ABSTRACT: Background and objective : The prevalence of potentially inappropriate prescribing (PIP) among nursing home (NH) residents is high. This study aimed to investigate the acceptance and implementation of pharmacist recommendations based on a screening tool for PIP, the Ghent Older People's Prescriptions community Pharmacy Screening (GheOP 3 S)-tool. Setting and method : Prospective observational study in NH residents (≥ 70 years, using ≥ 5 medications) with a 3-month follow-up period. A pharmacist screened the medication lists using the GheOP 3 S-tool and formulated recommendations to reduce PIP. The acceptance of recommendations discussed during face-to-face pharmacist-general practitioner (GP) meetings was recorded. Implementation was examined by comparing baseline and follow-up medication lists. A pre-post comparison of the number of chronic medications and GheOP 3 S-criteria; the anticholinergic and sedative burden quantified by the Drug Burden Index (DBI); and medication costs was performed. Results : Screening with the GheOP 3 S-tool resulted in 168 pharmacist recommendations for 50 NH residents, mainly to stop (78.0%) and to substitute (14.3%) medications. Ninety-three % (156/168) of recommendations were considered relevant. GPs acceptance rate was 44.9%. Fifty-four % of all accepted recommendations were implemented. At follow-up, the number of chronic medications (p = 0.007), and DBI scores (p = 0.004) significantly differed from baseline. There was no significant decrease in the number of GheOP 3 S-criteria (p = 0.075) and medication costs (p > 0.05). Conclusion : The acceptance and implementation of pharmacist recommendations were relatively low. Future studies should increase the involvement of patients and all health-care providers. Interdisciplinary collaboration with sufficient education for all disciplines and patients is essential.